2009
DOI: 10.1071/ea08184
|View full text |Cite
|
Sign up to set email alerts
|

Composite trait selection to improve reproduction and ewe productivity: a review

Abstract: Abstract. Reproduction and ewe productivity are complex composite traits that are influenced by several component traits. Genetic improvement by selection for an individual component trait may not always be advantageous because adverse or neutral genetic relationships can exist among the component traits. Selection for an overall composite trait of ewe productivity, defined as litter weight weaned per ewe joined, can result in a balanced biological composite trait with favourable responses in component traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Sustainable sheep production systems are based on valuable lamb sold per ewe exposed to rams under balanced cost of production (Lupton, 2008;Snowder and Foggarty, 2009;Fogarty, 2009). Under this context prolificacy and survival of twin lambs have the most critical impact in sheep productivity (Young et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable sheep production systems are based on valuable lamb sold per ewe exposed to rams under balanced cost of production (Lupton, 2008;Snowder and Foggarty, 2009;Fogarty, 2009). Under this context prolificacy and survival of twin lambs have the most critical impact in sheep productivity (Young et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier investigations (Dickerson, 1970) have stressed the importance of reproduction and mothering ability of ewes, and growth and survival of lambs for efficient lamb production to satisfy the demand for quality wool and meat by consumers. Research has suggested the possibility of improving ewe reproduction genetically through direct and indirect selection because of its composite nature (Olivier et al, 2001;Cloete, 2002;Snowder & Fogarty, 2009). However, it was contended that selection for a component of a composite trait does not always result in an overall improvement of a complex trait such as ewe reproduction (Snowder & Fogarty, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested the possibility of improving ewe reproduction genetically through direct and indirect selection because of its composite nature (Olivier et al, 2001;Cloete, 2002;Snowder & Fogarty, 2009). However, it was contended that selection for a component of a composite trait does not always result in an overall improvement of a complex trait such as ewe reproduction (Snowder & Fogarty, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…But genetic progress is not exclusively depending on the estimate of heritability for a specific, and also reliant on generation interval, intensity of selection, and the genetic variance for a trait (Brien et al 2010). Genetic progress for survival trait in sheep would be improved by possible methods, including the implementation of indirect selection through direct selection for more heritable trait which have high genetic correlation with survival traits, progeny testing of sires, selection on the basis of the total weaning weight of lambs and application of other relatives information in genetic evaluations (Snowder and Fogarty 2009;Brien et al 2010). In addition, Hatcher et al (2010) suggested that genetic gains would be possible for lamb survival through using repeated measurements.…”
Section: Discussionmentioning
confidence: 99%